Adverse socioeconomic position during the life course is associated with multiple sclerosis. Issue 7 (27th February 2014) - Briggs, Farren B S; Acuña, Brigid S; Shen, Ling; Bellesis, Kalliope H; Ramsay, Patricia P; Quach, Hong; Bernstein, Allan; Schaefer, Catherine; Barcellos, Lisa F
Abstract : Background: Adverse socioeconomic position (SEP) in childhood and adulthood is associated with a proinflammatory phenotype, and therefore an important exposure to consider for multiple sclerosis (MS), a complex neuroinflammatory autoimmune disease. The objective was to determine whether SEP over the life course confers increased susceptibility to MS. Methods: 1643 white, non-Hispanic MS case and control members recruited from the Kaiser Permanente Medical Care Plan, Northern California Region, for which comprehensive genetic, clinical and environmental exposure data have been collected were studied. Logistic regression models investigated measures of childhood and adulthood SEP, and accounted for effects due to established MS risk factors, including HLA-DRB1*15:01 allele carrier status, smoking history, history of infectious mononucleosis, family history of MS and body size. Results: Multiple measures of childhood and adulthood SEP were significantly associated with risk of MS, including parents renting versus owning a home at age 10 : OR=1.48, 95% CI 1.09 to 2.02, p=0.013; less than a college education versus at least a college education based on parental household : OR=1.28, 95% CI 1.01 to 1.63, p=0.041; low versus high life course SEP : OR=1.50, 95% CI 1.09 to 2.05, p=0.012; and low versus high social mobility : OR=1.74, 95% CI 1.27 to 2.39, p=5.7×10 −4 . Conclusions: Results derived from a population-representative case–control study provide support for the role of adverse SEP in MS susceptibility and add to the growing evidence linking lower SEP to poorer health outcomes. Both genetic and environmental contributions to chronic conditions are important and must be characterised to fully understand MS aetiology.